Anatomy of Hasupa Hasundau Hapakat (H3) as a lawmaking system - SABIAN, U. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper seeks to address, first, the characteristics of the society in Palangka Raya with the Huma, second, the conflicts in Palangka Raya, and third, synergy between the lawmaking. The research was carried out using the sociology of law with Emik perspective and with 63 informants involved through observation and document study. Findings show the following: First, Palangka Raya is one of the 14 districts and Central Kalimantan comprises 5 districts and 30 villages with Huma Betang culture inherited from the Dayak. Second, among the reasons for violence are economic development, religion, culture, and politics. RESUMEN Este documento busca abordar, primero, las características de la sociedad en Palangka Raya con los Huma, segundo, los conflictos en Palangka Raya, y en tercer lugar, sinergia entre la legislación. La investigación se llevó a cabo utilizando la sociología del derecho con perspectiva Emik y con 63 informantes involucrados a través de la observación y el estudio de documentos. Los hallazgos muestran lo siguiente: Primero, Palangka Raya es uno de los 14 distritos y Kalimantan Central comprende 5 distritos y 30 aldeas con cultura Huma Betang. En segundo lugar, entre las razones de la violencia se encuentran el desarrollo económico, la religión, la cultura y la política.